Sustainability analysis of the tourism system in El Capulín community, Monarch Butterfly Biosphere Reserve - Villafaña-Rivera, Francisco Joaquin; Zepeda-Bautista, Rosalba; Flores-Amador, Cristina (Amazonia Investiga, 2025)
The construction of indicators allows us to detect critical points of the analyzed system, to detect causes and provide solutions. In the tourism area, the indicators are limited, although their application helps to quantify the functioning of the destination and generate strategies that benefit those involved. The objective of this research was to carry out an analysis of the sustainability of producers in El Capulín community using indicators in dimensions; economic, social and environmental with the purpose of generating a baseline in the sustainable area, which serves for rural development, supported under the Framework for the Evaluation of Natural Resource Management Systems incorporating Sustainability Indicators. A structured survey was designed, referring to tourist activity, applied with intentional sampling to 63 ejidatarios. The statistical analysis generated six indicators in the economic dimension, six environmental and ten social, the evaluation of the system allowed us to know that the PSTP group has 65.03% sustainability, while the PSTM group has 85.25%, the interaction in the system showed that Tourism is not an economic activity that provides a good quality of life to those interested, therefore, increase your knowledge as a strategy to improve your performance and skills.